CALCULATION OF MATRIX MULTIPLES - Sh. X. Zikiryayev (European Science Publishing, 2024)
This article provides information that is useful to high school students, including calculating the characteristic equation of matrixes, finding their own numbers and vectors, methods of calculating matrix multiples, and the necessary formulas. Thisinformation can be used to calculate engineering issues.
Keywords: matrix, characteristic equation, unique number, specific vector, matrix multiplicity